Mechanisms for enhanced transition boiling during quenching on a superhydrophilic surface as revealed by in situ characterization on the solid-liquid contact using electrochemical impedance technique. (February 2020) - Zhang, Jia-Yi; Fan, Li-Wu; Li, Jia-Qi; Jiang, Le-Yi; Yu, Zi-Tao
Highlights: Electrochemical impedance technique was used to characterize solid-liquid contact. Electrochemical impedance model was built for a sphere submerged in an electrolyte. Solid-liquid contact during quenching on a superhydrophilic surface was determined. Contact proportion in transitional film boiling sub-regime was measured to be 0.1. This gives an evidence for the hypothesized "point-to-surface" contact transition. Abstract: The existence of two "transition" boiling curves has been discovered for over three decades, and has recently been re-examined in the investigations of quenching on superhydrophilic surfaces with enhanced boiling heat transfer, where the stable film boiling regime usually disappears and a significantly extended transitional film boiling sub-regime emerges instead, leading to a two-section shape of the transition boiling curve. It was hypothesized that the critical point at the slope change on the transition boiling curve is related to the transition in intensity/frequency of the solid-liquid contact status. Although it sounds rational, this hypothesis has not yet been proved due to the lack of a quantitative characterization on the solid-liquid contact. In this work, the electrochemical impedance technique was employed to perform in situ measurements on the interfacial solid-liquid contact during quenching on a superhydrophilic surface (over a stainless steel ball) in a very dilute aqueous electrolyte. It was found that the solid-liquid contact proportion in the transitional film boiling sub-regime is around 0.1, which becomes much greater in the transitional nucleate boiling sub-regime. This corresponds to a sharp increase on the contact proportion curve, which was found to occur in accordance with the transition in the boiling curve. The measured proportions thus provide an intuitive evidence to verify, for the first time in the literature, the hypothesized transition of solid-liquid contact mode from "point-contact" to "surface-contact" in the transition boiling regime. This method can be used to give more insights into the mechanisms for enhanced boiling heat transfer on superhydrophilic surfaces with novel micro-/nanostructures.